Generation of a recombinant Moloney murine leukemia virus carrying the v-src gene of avian sarcoma virus: transformation in vitro and pathogenesis in vivo. - Feuerman, M H (1985)
A Moloney murine leukemia virus (M-MuLV) recombinant carrying the v-src gene of avian sarcoma virus was generated by the introduction of a cloned portion of v-src from Schmidt-Ruppin A avian sarcoma virus into a molecular clone of M-MuLV provirus at the recombinant DNA level. The v-src sequences (lacking a portion of the 5' end of v-src) were inserted into the p30 region of the M-MulV gag gene so that M-MuLV gag and v-src were in the same reading frame. Transfection of this chimeric clone, pMLV(src), into NIH 3T3 cells which were constitutively producing M-MuLV gag and pol protein resulted in the formation of foci of transformed cells. Infectious and transforming virus could be recovered from the transformed cells. This virus was designated M-MuLV(src). M-MuLV(src)-transformed cells contained two novel proteins of 78 and 90 kilodaltons. The 78-kilodalton protein, p78gag-src, contained both gag and src determinants, exhibited kinase activity in an immune kinase assay, and is probably a fusion of Pr65gag and src. The 90-kilodalton protein, which is of the appropriate size to be the gPr80gag fused to src, contained gag determinants as well as a V8 protease cleavage fragment typical of the carboxy terminus of avian sarcoma virus pp60src. However, it could not be immunoprecipitated with an anti-v-src serum. M-MuLV(src)-transformed cells showed elevated levels of intracellular phosphotyrosine in proteins, although the elevation was intermediate compared with cells transformed with wild-type v-src. M-MuLV and amphotropic murine leukemia virus pseudotypes of M-MuLV(src) were inoculated into newborn NIH Swiss mice. Inoculated mice developed solid tumors at the site of inoculation after 3 to 6 weeks, with most animals dying by 14 weeks. Histopathological analysis indicated that the solid tumors were mesenchymally derived fibrosarcomas that were both invasive and metastatic.